Biomimetic phospholipid polymers for suppressing adsorption of saliva proteins on dental hydroxyapatite substrate. Issue 6 (7th September 2020) - Ishihara, Kazuhiko; Kozaki, Yoichiro; Inoue, Yuuki; Fukazawa, Kyoko
Abstract: To prevent infectious diseases induced by the adhesion of microorganisms and their metabolic products to dental implants, saliva protein adsorption, which induces the plaque deposition to the intraoral substrates should be inhibited. We used a water‐soluble 2‐methacryloyloxyethyl phosphorylcholine (MPC) polymer to modify the surface of hydroxyapatite (HAp) substrate, the main component of dental implant surface. The MPC polymer containing a catechol group at the terminal of polymer chain and amino groups in the side chain was synthesized by mimicking the mussel adhesive protein. The MPC polymer containing 2% of the primary amino groups showed effective adhesion to the HAp substrate. Mucin, the dental plaque protein, adsorbs on the HAp surface; however, the MPC polymer modification could reduce this adsorption amount by more than 98% compared to the original HAp substrate surface. Thus, the treatment of the MPC polymer has potential to reduce oral infection due to plaque deposition. Abstract :